ESG and firm value: The moderating role of environmental performance and profitability in Indonesia’s mining sector - Oktadewi, Angelina Metta Arilia; Diantini, Ni Nyoman Ayu (International research journal of management, IT and social sciences, 2025)
This study examines the relationship between Environmental, Social, and Governance (ESG) performance and firm value in Indonesia’s mining sector, with a focus on the moderating roles of environmental performance and profitability. ESG performance is proxied by the Sustainable Report Disclosure Index (SRDI), firm value is measured using Tobin’s Q, environmental performance is measured using the PROPER rating, and profitability is represented by Return on Assets (ROA). The research sample comprises 10 mining companies listed on the Indonesia Stock Exchange (IDX) that consistently publish sustainability reports and participate in the government’s PROPER environmental compliance rating program, observed over 4 years (2020–2023), resulting in 40 firm-year observations. The study employs panel data regression with a random effects model, based on the results of the Chow, Hausman, and Lagrange Multiplier tests. The findings reveal that ESG performance has a negative and statistically significant effect on firm value. Furthermore, profitability significantly moderates the relationship between ESG and firm value, while environmental performance does not show a moderating effect. These results suggest that investors may view ESG initiatives as costly when not supported by strong financial performance.